2022
DOI: 10.1097/txd.0000000000001334
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Elastography-derived Stiffness Predicts Renal Function Loss and Is Associated With Microvascular Inflammation in Kidney Transplant Recipients

Abstract: Background. Organ stiffening can be caused by inflammation and fibrosis, processes that are common causes of transplant kidney dysfunction. Magnetic resonance elastography (MRE) is a contrast-free, noninvasive imaging modality that measures kidney stiffness. The objective of this study was to assess the ability of MRE to serve as a prognostic factor for renal outcomes. Methods. Patients were recruited from the St Michael's Hospital Kidney Transplant Clinic. Relevant baseline demographic, clinical, and Banff hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Therefore, reduced stiffness can be linked to reduced blood flow, a surrogate for fibrosis, which per se increases stiffness (Lee et al, 2012;Kline et al, 2018;Lang et al, 2019;Marticorena Garcia et al, 2019;Brown et al, 2020;Zhang et al, 2021;Güven et al, 2022). But other studies found an increase in stiffness with (suggested) higher levels of fibrosis (Marticorena Kirpalani et al, 2017;Han et al, 2020;Elsingergy et al, 2023) or inflammation (Shatil et al, 2022). Therefore, measuring fasting and hydration related changes in patients could be a useful tool to unveil insights into pathophysiological processes.…”
Section: Hydration-related Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, reduced stiffness can be linked to reduced blood flow, a surrogate for fibrosis, which per se increases stiffness (Lee et al, 2012;Kline et al, 2018;Lang et al, 2019;Marticorena Garcia et al, 2019;Brown et al, 2020;Zhang et al, 2021;Güven et al, 2022). But other studies found an increase in stiffness with (suggested) higher levels of fibrosis (Marticorena Kirpalani et al, 2017;Han et al, 2020;Elsingergy et al, 2023) or inflammation (Shatil et al, 2022). Therefore, measuring fasting and hydration related changes in patients could be a useful tool to unveil insights into pathophysiological processes.…”
Section: Hydration-related Changesmentioning
confidence: 99%
“…This hydrostatic pressure enables a relatively constant filtration of blood in the glomeruli, i.e., glomerular filtration rate (∼120 mL/min; GFR). Therefore, quantifying biomechanical properties—even with contributions from perfusion and fibrosis—has the potential to assess kidney function ( Marticorena Garcia et al, 2016 ; Kirpalani et al, 2017 ; Marticorena Garcia et al, 2018a ; Lang et al, 2019 ; Beck-Tölly et al, 2020 ; Brown et al, 2020 ; Zhang et al, 2021 ; Chen et al, 2022 ; Shatil et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For magnetic resonance elastography (MRE), a number of studies investigating disorders of abdominal organs such as liver (15)(16)(17)(18)(19)(20)(21)(22), spleen (23)(24)(25), kidney (26)(27)(28)(29), and pancreas (30)(31)(32)(33)(34) have been performed. However, studies investigating MRE of the gastrointestinal tract are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Renal perfusion, as another important contributor to renal stiffness, was also suggested by others in. 7,9 Very recently, Shatil et al 10 reported that renal stiffness quantified by MRE was positively associated with microvascular inflammation. Based on the literature, there appears to be a multifactorial influence of CKD-related pathological features on in vivo renal stiffness that could be explored further with animal models.…”
Section: Introductionmentioning
confidence: 99%